Perbandingan Hasil Belajar IPS dengan Menggunakan Numbered Head Together dan Snowball Throwing - Rizky Ika Puspitasari; I Komang Winatha; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2018)
This research object was to find out the difference life skill, interaction in Numbered Head Together  learning model  and Snowball Throwing by seeing the task techique. The Research method was quasi experiment by appraoching comparatively. Data collecting technique which used in this research was observation and analysed by using t-test formula and N-Gain  SPSS. This research was done in SMPN 1 Kragilan with the population 9 classes and 2 classes as samples (VIIB and VIIF) which determined through cluster random sampling. The result of the analysis showed F count F table or 3,873 1,667 means there is difference life skills through NHT learning model and ST  Avarage learning outcomes of ips which is taught by using model type NHT is higher compared with the learning usingTujuan penelitian ini yaitu untuk mengetahui hasil belajar penggunaan model pembelajaran Numbered Head Together dan Snowball Throwing. Metode penelitian yang digunakan dalam penelitian ini adalah eksperimen semu dengan pendekatan komparatif. Pengumpulan data melalui test dan dianalisis dengan rumus t-test dan n-Gain menggunakan SPSS. Penelitian ini dilakukan di SMPN 1 Kragilan dengan populasi sebanyak 9 kelas dan sampel 2 kelas (VII B dan VII F) yang ditentukan melalui Cluster Random Sampling. Hasil analisis data menunjukkan t hitung    ttabel atau 3,873  1,667 berarti ada perbedaan evektivitas  yang pembelajaranya yang mengunakan model pembelajaran kooperatif Numbered Head Together dan Snowball Throwing . Kata kunci:  Model Pembelajaran Kooperatif, NHT.ST, Hasil Belajar